ATP Synthase β-Chain Overexpression in SR-BI Knockout Mice Increases HDL Uptake and Reduces Plasma HDL Level - Kexiu Song; Yingchun Han; Linhua Zhang; Guoqing Liu; Peng Yang; Xiaoyun Cheng; Le Bu; Hui Sheng; Shen Qu (International Journal of Endocrinology)
HDL cholesterol is known to be inversely correlated with cardiovascular disease due to its diverse antiatherogenic functions. SR-BI mediates the selective uptake of HDL-C. SR-BI knockout diminishes but does not completely block the transport of HDL; other receptors may be involved. Ectopic ATP synthase β-chain in hepatocytes has been previously characterized as an apoA-I receptor, triggering HDL internalization. This study was undertaken to identify the overexpression of ectopic ATP synthase β-chain on DIL-HDL uptake in primary hepatocytes in vitro and on plasma HDL levels in SR-BI knockout mice. Human ATP synthase β-chain cDNA was delivered to the mouse liver by adenovirus and GFP adenovirus as control. The adenovirus-mediated overexpression of β-chain was identified at both mRNA and protein levels on mice liver and validated by its increasing of DiL-HDL uptake in primary hepatocytes. In response to hepatic overexpression of β-chain, plasma HDL-C levels and cholesterol were reduced in SR-BI knockout mice, compared with the control. The present data suggest that ATP synthase β-chain can serve as the endocytic receptor of HDL, and its overexpression can reduce plasma HDL-C.